MODERN DIAGNOSTIC METHODS OF CHLAMYDIA 4TH STAGE STUDENTS OF TASHKENT MEDICAL ACADEMY - Sharipov Akramxon; Vaxobjonova Guljahon; Sotivoldiyeva Nilufar; Ibodullayeva Dilsora (Western European Studies, 2024)
Modern diagnostic methods for chlamydia, particularly Chlamydia trachomatis, have evolved significantly and include several approaches. Here are some of the most commonly used methods: Nucleic Acid Amplification Tests (NAATs), PCR (Polymerase Chain Reaction), LAMP (Loop-mediated Isothermal Amplification), Swab Tests, Serological Tests, Rapid Tests,Point-of-Care Testing,Combination Testing. The organization of modern diagnostic methods for chlamydia is a multifaceted approach that balances accuracy, accessibility, speed, cost, and patient-centered care. By considering these factors, healthcare providers can effectively diagnose and manage chlamydia infections, ultimately contributing to better sexual health outcomes in the population
Keywords: infections; Testing; organization; Amplification